Invertebrate zoology : - Ruppert, Edward E. (Saunders College Publishing, 1994)
Organized by taxa, this textbook characterizes the phylogeny and biology of protozoa, metazoa, eumetazoa, bilateria, and anthropoda. The seventh edition adds five chapters that introduce each section of the book and present the functional evolutionary approach to invertebrate diversity.